(untitled) (Książnica Śląska, 2025)
The Silesian Branch of the Polish Historical Society was founded in 1929 on the initiative of the Silesian Voivode Michał Grażyński, historian Roman Lutman, and head of the Department of Public Education in Katowice, Ludwik Ręgorowicz. Their main objective was to support Silesian historical research and promote knowledge about the history of Silesia. This article presents the process of establishing the Silesian branch of society and its main activities, such as lectures, research work, and didactics. Additionally, it discusses the branch’s collaboration with other scientific and cultural institutions in Upper Silesia during the interwar period, including the Society of Friends of Science in Silesia and the Institute of Silesia. The author also mentions the participation of the members in the Universal Congress of Polish Historians.